Developing a Fragility Framework for Supply Chain and Outsourcing Engineering Services in UAE - Ababneh, Thamer (2019)
This research analyzes the risk and fragility factors which are affecting the outsourcing services in the UAE market concentrating on the risk events and its impacts on fragility. Different organizations have different needs or factors that drive their decision related to outsourcing. The research aimed to analyze the risks which affect the implementation of outsourcing and to identify the characteristics to build a fragility framework for the outsourcing of engineering services. The analyses were carried out based on process, people, systems, and external factors and attempted to specify the risk events that influence on outsourcing fragility and develop the outsourcing fragility framework for engineering services enterprises. This framework can be utilized by the company decision-makers to manage fragility as well as deal with the various risk events, both pre and post outsourcing decisions. Results showing how main risk factors influence the risk and fragility and assist firms where to focus when outsourcing needs to be decided or improved to avoid threats, harm reputation or financial loss, etc. The research findings showed that if companies can develop a strategy for outsourcing that addressed the limitation and challenges, the firms can get many benefits that come with outsourcing. Firms can save on time, get an enhanced quality of product, save cost, and gain performance enhancements that can provide the firms with the flexibility and capability to get better projects. There is potential to researchers to find how to minimize the risks and fragility to improve the supply chain and firms to decide for outsourcing their services with higher quality and less cost. Researchers can focus for specific industry for more coherent analysis and find relation between fragility and resilience.